Critical librarianship - Hines, Samantha Schmehl; Ketchum, David (Emerald Publishing Limited, 2020)
Librarianship has always had links with critical theory. As a public service, libraries cannot be separated from the society they exist in, and investigating the aspects of the culture they exist in is an important responsibility for all library and information professionals. In this exciting exploration of critical librarianship, expert authors from different walks of life investigate a variety of areas of librarianship in regards to critical theory. With chapters on feminist theory, sustainability and social justice, inclusivity, autism, and new motherhood, among others, this volume of Advances in Librarianship focuses on some of the most relevant issues of the 21st Century. With rigorous scholarship and diverse voices, Critical Librarianship is an unmissable volume of current research for all library and information professionals and researchers.
Chapter 1: Introduction: Critical Librarianship; David H. Ketchum -- Chapter 2: Theoretical and Practical Implications of Power Dynamics in Academic Libraries; Lilian Ingutia Oyieke -- Chapter 3: Widening Participation Praxis and Library Leadership; Andrew Preater -- Chapter 4: Feminists at Work: Organizational Leadership in Academic Libraries; Freeda Brook and Martinique Hallerduff -- Chapter 5: From Street-Level Bureaucracy to Sustainable Communities: Librarianship for Social Justice in Times of Limited Resources; Yolanda Patrice Jones -- Chapter 6: Looking Beyond Libraries for Inclusive Recruitment and Retention Practices: Four Successful Approaches; Jade Alburo, Agnes K. Bradshaw, Laura Lillard, Ariana E. Santiago, Bonnie Smith, and Jennifer Vinopal -- Chapter 7: Countering Conformity: Embracing the 'Other' and Supporting Employees with High-Functioning Autism in Canadian Academic Libraries; Lori Giles-Smith and Emma Popowich -- Chapter 8: Going Back to Work: How Supervisors Can Support New Mothers as They Transition Back to the Library; Emily A. B. Swanson -- Chapter 9: Teamwork, Emotional Intelligence, and the Skills Organizations Need Now; John A. Lehner.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Libraries and society; Critical theory; Language Arts & Disciplines -- Library & Information Science -- Administration & Management; Community & outreach services